2013
DOI: 10.4236/ojmc.2013.34012
|View full text |Cite
|
Sign up to set email alerts
|

Piericidins, Novel Quorum-Sensing Inhibitors against Chromobacterium violaceum CV026, from Streptomyces sp. TOHO-Y209 and TOHO-O348

Abstract: Piericidin A1, 3'-rhamnopiericidin A1, and a novel compound piericidin E, a new quorum-sensing (QS) inhibitor against Chromobacterium violaceum CV026, were isolated from the culture broth of Streptomyces sp. QS is well known as a microbial signaling system and controls certain types of gene expression resulting in bioluminescence, biofilm formation, swarming motility, antibiotic biosynthesis, and virulence factor production. C. violaceum CV026 is commonly used to determine qualitative and quantitative QS activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…Similarly, previous studies reported the isolation and the characterization of QSI compounds from Streptomyces isolates such as cinnamic acid and dipeptide proline–glycine from a marine invertebrate Streptomyces ( Naik et al, 2013 ). Also, Streptomyces TOHO-O348 and TOHO-Y209 produce piericidins with a marked QSI effect on C. violaceum CV026 ( Ooka et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies reported the isolation and the characterization of QSI compounds from Streptomyces isolates such as cinnamic acid and dipeptide proline–glycine from a marine invertebrate Streptomyces ( Naik et al, 2013 ). Also, Streptomyces TOHO-O348 and TOHO-Y209 produce piericidins with a marked QSI effect on C. violaceum CV026 ( Ooka et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several Actinobacteria have the ability to colonize plant surfaces and thereby exclude plant pathogens either by competition or through inhibition by antibiotic production ( Selvakumar et al, 2014 ). Over the last decade, a total of six actinobacterial genera: Arthrobacter ( Flagan et al, 2003 ), Microbacterium ( Wang et al, 2012 ), Mycobacterium ( Chen and Xie, 2011 ), Nocardioides ( Yoon et al, 2006 ), Rhodococcus ( Park et al, 2006 ; Latour et al, 2013 ), and Streptomyces ( Chen and Xie, 2011 ; Ooka et al, 2013 ) have been reported for their quorum quenching activity. Members of these genera known to exist as plant symbionts or as endophytes residing within plant hosts without causing disease symptoms are reported to produce AHL-inactivating enzymes.…”
Section: Quorum Quenching Activity In Actinobacteriamentioning
confidence: 99%
“…Similarly, a major metabolite piericidin A1 secreted by Streptomyces sp. TOHO-Y209 and TOHO-O348 demonstrated quorum sensing inhibiting activity against C. violaceum CV026 ( Ooka et al, 2013 ). The piericidin class of metabolites are known inhibitors of NADH-ubiquinone oxidoreductase, with A1 specifically inhibiting both mitochondrial and bacterial NDAH- ubiquinone oxidoreductases.…”
Section: Quorum Quenching Activity In Actinobacteriamentioning
confidence: 99%
“…Bacterial Strains, Media, and Culture C. violaceum CV026 14) was cultured in Luria Broth [LB; 1.0% Bacto tryptone (Becton, Dickinson and Company, Sparks, MD, U.S.A.), 0.5% Bacto yeast extract (Becton, Dickinson and Company), and 0.5% NaCl (Wako Pure Chemical Corporation, Osaka, Japan), pH 7.2] at 27°C. P. aeruginosa ATC C 27853, 17) a quality control strain for dilution antimicrobial susceptibility tests, was cultured overnight in Nutrient Broth (NB; Eiken Chemical Co., Ltd., Tochigi, Japan) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Based on these novel "anti-infective drugs," we previously established a screening system using Chromobacterium violaceum CV026 14) to identify QS inhibitors produced by actinomycetes. Piericidin E, a novel compound, was recently discovered in Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%